2016
DOI: 10.1055/s-0036-1584910
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Care in Disaster-Affected Areas: A Firsthand Perspective after Typhoons Bopha and Haiyan in the Philippines

Abstract: Disasters are defined as man-made or natural causes that disrupt a population and cause widespread human, material, economic, or environmental losses, exceeding that population's capacity to cope using its own resources. This review highlights the epidemiology and disease patterns in disasters, with specific application to the care of children in the austere environments created in the aftermath of disasters. The review also attempts to describe the experience from a firsthand field hospital perspective of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Out of 9 disaster medicine articles, 8 were about the Typhoon Haiyan disaster that hit the central Philippines in November 2013 58 . These Typhoon Haiyan articles had the following themes: mental health care, 41 pediatric care during disasters, 44 foreign medical team registration, 40 diabetes care, 43 and documentation of medical needs 45 . There were also 3 field reports and commentaries from the United States, Korea, and China that discussed the aid extended by their respective countries as they sent medical rescue teams 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Out of 9 disaster medicine articles, 8 were about the Typhoon Haiyan disaster that hit the central Philippines in November 2013 58 . These Typhoon Haiyan articles had the following themes: mental health care, 41 pediatric care during disasters, 44 foreign medical team registration, 40 diabetes care, 43 and documentation of medical needs 45 . There were also 3 field reports and commentaries from the United States, Korea, and China that discussed the aid extended by their respective countries as they sent medical rescue teams 37–39 .…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% were discharged directly home. A Non-Governmental Organisation (NGO) field hospital deployed following Typhoons Bopha and Haiyan in the Philippines reported 27% of their patients were four years old or younger, with the most common diagnoses being upper respiratory tract infections, gastroenteritis, dehydration, rashes and injuries 3. Despite being in place primarily to treat military personnel, a review of all casualties seen in US combat support hospitals and forward surgical teams in Afghanistan and Iraq between 2001 and 2011 revealed that children represented 5.8% of admissions and 11% of total bed days.…”
Section: Interventionsmentioning
confidence: 99%
“…Conflict and civil unrest, ongoing or arising after a disaster, add to the complexity and diminish a community’s ability to cope, as well as impact on the availability of external support. Whichever way we choose to classify them, disasters have been increasing in frequency, with an estimated 4.03 billion people affected over the past 20 years2 and around 50% of those affected under the age of 18 3. Developing countries with lower economic resilience to disasters tend to have higher fertility rates and a younger population structure, further increasing the risk to children.…”
Section: Introductionmentioning
confidence: 99%